2015
DOI: 10.1016/j.mseb.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

SnO2/reduced graphene oxide composite films for electrochemical applications

Abstract: SnO 2 /GO (GO is graphene oxide) composite films with GO mass fraction w C ranging from 0.01 to 80% have been prepared using colloidal solutions. Heat treatment of SnO 2 /GO films in Ar atmosphere at 400 • C leads to GO reduction accompanied by partial exfoliation and decreasing of the particle thickness. SnO 2 /rGO (rGO is reduced GO) film electrodes demonstrate a high electrocatalytic activity in the anodic oxidation of inorganic (iodide-, chloride-, sulfite-anions) and organic (ascorbic acid) substances. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The decrease of the I D /I G ratio in the SG-E and SG-C suggested the removal of oxygenated groups and the restoration of the sp 2 carbon atoms during the thermal treatment process [43,44]. Thus, it could be concluded that GO in the core-shell structures could be effectively reduced via the thermal treatment process, which was consistent with the results of FTIR and XPS.…”
Section: Resultssupporting
confidence: 83%
“…The decrease of the I D /I G ratio in the SG-E and SG-C suggested the removal of oxygenated groups and the restoration of the sp 2 carbon atoms during the thermal treatment process [43,44]. Thus, it could be concluded that GO in the core-shell structures could be effectively reduced via the thermal treatment process, which was consistent with the results of FTIR and XPS.…”
Section: Resultssupporting
confidence: 83%
“…[ 39 ] In comparison, ATO/GO features additional weight loss steps at 220 °C related to the loss of oxygen containing groups on the surface of GO. [ 40 ] The weight fraction of the ATO phase in the ATO/C/rGO and ATO/C‐2/rGO composites is much lower, equaling 65 and 54 wt%, respectively, due to the additional carbon coating (Figure 1b and Figure S4b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The TGA curves of GO in air show a weight loss at around 200 °C and between 500 and 600 °C (Figure b) due to the combustion of oxygen‐containing groups and the gradual decomposition of the GO, respectively . In contrast, rGO shows practically no weight loss in the range of 25–250 °C due to the absence of oxygen groups and only a small amount of adsorbed or weakly bound residues.…”
Section: Resultsmentioning
confidence: 99%